Entrepreneurship: Pioneering the Transformation of Modern Business Strategy (Global Journal of Management and Business Research, 2023)
This article delves into the enormous effect that entrepreneurial spirit has on modern company strategy This article provides an in-depth look at some of the most important facets of entrepreneurship including its origins disruptive nature technology developments customer-centric approaches collaborative ecosystems risk management scaling and lessons from successful entrepreneurs Entrepreneurship has reshaped the way businesses operate by stimulating innovation testing the status quo of established industries and opening up fresh sales channels Steve Jobs Jeff Bezos Elon Musk Sara Blakely and Mark Zuckerberg are just a few examples of successful entrepreneurs who have transformed their respective sectors by a combination of consumer focus technological innovation resourcefulness and resilience This article provides a glimpse into the future of entrepreneurship and company strategy by highlighting rising themes Key drivers of entrepreneurship are innovation enabled by technology as well as sustainability globalisation collaboration and adaptability Entrepreneurs may generate good change create value and deal with the uncertainties of today s difficult business climate by capitalising on these trends The article finishes by stressing the value of an entrepreneurial frame of mind and approach no matter the size or nature of the business
Keywords: entrepreneurship; modern business strategy; transformation; innovation; disruption; technology; customer-centric; collaboration; risk management